Woodland restoration on agricultural land: long‐term impacts on soil quality. Issue 6 (5th August 2019) - Ashwood, Frank; Watts, Kevin; Park, Kirsty; Fuentes‐Montemayor, Elisa; Benham, Sue; Vanguelova, Elena I.
Abstract : Woodland restoration is underway globally to counter the negative soil quality and ecological impacts of agricultural expansion and woodland fragmentation, and restore or enhance biodiversity, ecosystem functions and services. However, we lack information about the long‐term effects of woodland restoration on agricultural soils, particularly at temporal scales meaningful to woodland and soil development. This study utilized soil and earthworm sampling across a chronosequence of sites transitioning from "agricultural land" to "secondary woodland" (50–110 years) and "ancient woodland" (>400 years), with the goal of quantifying the effects of woodland restoration on agricultural land, on key soil quality parameters (soil bulk density, pH, carbon and nitrogen stocks, and earthworm abundance, biomass, species richness and diversity). Broad‐leaved woodland restoration led to significantly greater soil organic carbon (SOC) stocks compared to arable land, and young (50–60 years) secondary woodland increased earthworm species and functional diversity compared to both arable and pasture agricultural land. SOC stocks in secondary broad‐leaved woodlands (50–110 years) were comparable to those found in long‐term ancient woodlands (>400 years). Our findings show that broad‐leaved woodland restoration of agricultural land can lead to meaningful soil ecological improvement and gains in SOC within 50–110 years, and provide intel on how restoration activities may be best targeted to maximize soil quality and functions.